Surface strengthening treatment process of float glass
By using a mixed acid solution of inorganic acid and organic acid in the oxygen-containing atmosphere of the float glass with sulfur dioxide and water, the problem of warping and deformation of the float glass during the strengthening treatment is solved, and the glass strength is improved and the warping phenomenon is improved.
Patent Information
- Application Number
- CN202411771885.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The existing floating glass surface reinforcement treatment process is difficult to solve the problem of glass warping and deformation while increasing the strength of the glass, and there are problems such as high processing cost, low efficiency, complex process and polluting the environment.
The float glass is placed in an oxygen-containing atmosphere containing sulfur dioxide and water, and a mixed acid solution of inorganic acid and organic acid is coated on the air surface of the glass for reinforcement treatment. By urging the strengthening reaction between the air surface and the tin surface of the glass, a dense structure is formed and surface stress is increased.
Significantly improve the strength and warping of float glass, avoid warping caused by excessive strength on one side of the glass, and at the same time reduce processing costs, improve process efficiency, and reduce pollution.
Smart Images

Figure CN119569356A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass production, and in particular to a surface strengthening treatment process for float glass. Background Art
[0002] As a brittle material, glass is prone to cracking and breaking. In order to ensure the safety factor and service life of glass, it needs to be chemically strengthened (also known as ion exchange strengthening) to improve the strength of glass. However, during the tin bath molding process of glass produced by float glass, the lower surface of the glass contacts the tin liquid and the upper surface contacts the air. The float glass after molding has an air side and a tin side. During chemical strengthening, the ion exchange amount of the air side and the tin side is different, which is prone to warping and deformation. This warping phenomenon will have a serious impact on the quality of glass products.
[0003] At present, the existing technology for treating tin surface mainly includes grinding or using strong acid, sulfide, nitride, inorganic acid to corrode SnO, SnO2 and other substances on the surface, and then ion exchange strengthening to avoid glass warping. However, the grinding method has problems such as high processing cost, low yield, low efficiency, complex process and difficult control; and the use of strong acid, sulfide, nitride, inorganic acid to treat the tin surface also has the problem of difficult control of the corrosion process, which is easy to cause ions on the surface of the glass, thereby reducing product quality, and the waste gas or waste liquid generated after corrosion is difficult to treat, and there is a problem of environmental pollution. Based on this, how to strengthen float glass to improve the strength of glass while solving the problem of glass warping and deformation is still an urgent problem to be solved. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing float glass surface strengthening treatment process is difficult to solve the problem of glass warping and deformation while improving the glass strength, thereby providing a float glass surface strengthening treatment process that solves the above problem.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A surface strengthening treatment process for float glass comprises: placing the float glass in an oxygen-containing atmosphere containing sulfur dioxide and water and applying acid liquid to the air surface of the float glass for strengthening treatment; the acid liquid is a mixed solution of an inorganic acid and an organic acid, and the molar ratio of the inorganic acid to the organic acid is 2:(3-4).
[0007] Preferably, during the strengthening process, the air side of the float glass faces upward.
[0008] Preferably, the oxygen-containing atmosphere comprises at least one of air and oxygen;
[0009] And / or, the coating is spraying;
[0010] And / or, the coating amount of the acid solution is 420-1250 g / m 2 .
[0011] Preferably, the volume content of the sulfur dioxide is 30-70%.
[0012] Preferably, the water content is 300-500 g / m 2 .
[0013] Preferably, the temperature of the strengthening treatment is 100 to 350°C;
[0014] And / or, the duration of the intensive treatment is ≥ 10 min, preferably, the duration of the intensive treatment is 10 to 120 min;
[0015] And / or, cooling and water washing are further performed after the strengthening treatment.
[0016] Preferably, the inorganic acid includes at least one of hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, nitric acid, and carbonic acid;
[0017] And / or, the organic acid comprises at least one of formic acid, acetic acid, propionic acid, oxalic acid, citric acid, glycolic acid, and acrylic acid;
[0018] And / or, a catalyst is further added to the acid solution, and optionally, the catalyst includes at least one of platinum, zinc, and aluminum, wherein platinum, zinc, and aluminum are all pure metals.
[0019] Preferably, the organic acid is acetic acid and oxalic acid;
[0020] And / or, the mass fraction of the platinum catalyst in the acid solution is 0.2-2%.
[0021] Preferably, the molar ratio of acetic acid to oxalic acid is 3:1.
[0022] Preferably, the mass fraction of the inorganic acid in the acid solution is 4 to 20%;
[0023] And / or, the solvent in the acid solution is water;
[0024] And / or, the float glass has a thickness of 0.5 to 2 mm.
[0025] The technical solution of the present invention has the following advantages:
[0026] 1. A surface strengthening process for float glass, comprising: placing the float glass in an oxygen-containing atmosphere containing sulfur dioxide and water and applying an acid solution to the air side of the float glass for strengthening treatment; the acid solution is a mixed solution of an inorganic acid and an organic acid, and the molar ratio of the inorganic acid to the organic acid is 2:(3-4). The present invention utilizes an oxygen-containing atmosphere containing sulfur dioxide and water to cause the air side and the tin side of the float glass to undergo strengthening reactions simultaneously, wherein the air side undergoes the following reactions in the atmosphere:
[0027] Na2O+SO2+1 / 2O2→Na2SO4 (1)
[0028] 2Na + +SO2+1 / 2O2+H2O→2H + +Na2SO4 (2)
[0029] Na2O+2H + →2Na + +H2O (3)
[0030] Through the above series of reactions, Na + ions into fusible salts, making the surface Na + The ions are reduced, and the purity of SiO2 and other components on the air surface is improved, forming a SiO2-rich layer, thereby forming a dense structure, becoming a low-expansion glass, and increasing the surface compressive stress; in this atmosphere, the Sn on the tin surface 2+ Oxidized to Sn 4+ , that is, 2SnO+O2→2SnO2, so that oxygen atoms enter the glass, and at the same time due to Sn 4+ The ionic radius is larger than Sn 2+ After oxidation, an extrusion effect is formed on the glass surface. Based on the embedding of oxygen atoms and the change of the radius of tin ions, a compressive stress layer is formed on the tin surface, thereby increasing the strength of the tin surface. At the same time, sulfur dioxide can also react with Na + Ion reaction, promoting the inner layer of Na + The ions migrate and diffuse to the surface, causing more vacancies inside the glass, and the tin ions migrate to the inside of the glass, thereby increasing the surface stress. The air surface is de-alkali treated by using a mixed acid solution of an inorganic acid and an organic acid with a molar ratio of 2: (3-4). + Filling the Na in the glass structure + The vacancies can be used to regulate the changes in the glass structure, thereby significantly improving the strength and warping of float glass, and avoiding warping caused by excessive strength on one side of the glass.
[0031] 2. In the strengthening process of the float glass of the present invention, the air side of the float glass faces upward during the strengthening process. This is because the density of SO2 is greater than that of air. During the strengthening process, some SO2 may fail to contact the Na2+ on the air side of the glass in time. + ions react and sink to the Na + The ions react to further improve the strength and warping of float glass.
[0032] 3. In the float glass strengthening process of the present invention, the acid solution is applied to the air surface of the float glass by spraying, and there is no need to immerse the float glass in the acid solution, thereby achieving surface strengthening of a large area of glass plate without the need for a container. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 It is a schematic diagram of strengthening the air surface of the float glass of the present invention;
[0035] Figure 2 It is a schematic diagram of strengthening the tin surface of float glass of the present invention;
[0036] Figure 3 It is a structural schematic diagram of the glass warpage test in Test Example 1 of the present invention;
[0037] Explanation of reference numerals: h - height of arc; L - length of chord. DETAILED DESCRIPTION
[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] The float glasses involved in the following embodiments and comparative examples are all prepared by the following steps: Na2O-CaO-SiO2 glass (glass thickness is 2 mm), Na2O-Al2O3-SiO2 glass (glass thickness is 2 mm). The preparation method of Na2O-CaO-SiO2 glass is as follows: according to the glass composition of 65% SiO2, 15% Na2O, 13% CaO, 5% Li2O, 2% ZnO, quartz sand, soda ash, calcium carbonate, lithium carbonate, zinc oxide and other raw materials are uniformly mixed and then put into a glass kiln, melted at a high temperature of 1300°C to form molten glass liquid, and the molten glass liquid is cooled to become glass to be strengthened. The preparation method of Na2O-Al2O3-SiO2 glass is as follows: according to the glass components of 75% SiO2, 12% Na2O, 5% Li2O, 4% Al2O3, 2% B2O3, 1% MgO, 1% CaO, quartz sand, soda ash, lithium carbonate, alumina and other raw materials are evenly mixed and put into a glass kiln, melted at a high temperature of 1380°C into molten glass liquid, and the molten glass liquid is cooled to become glass to be strengthened.
[0041] Example 1
[0042] This embodiment provides a surface strengthening process for float glass. Float glass is a Na2O-CaO-SiO2 glass. The strengthening principle of the air surface of float glass is as follows: Figure 1 As shown in the figure, the strengthening principle of the tin surface is as follows Figure 2 As shown, the specific steps are as follows:
[0043] 1) Place the float glass in an air atmosphere containing sulfur dioxide and water at a temperature of 200°C, wherein the volume content of sulfur dioxide is 55% and the volume content of water is 400g / m 2 , the float glass is placed with the air side facing upwards;
[0044] 2) A mixed solution of hydrochloric acid, acetic acid and oxalic acid in a molar ratio of 2:3:1 was added at 1000 g / m 2 The coating amount is sprayed on the air surface of the float glass, treated for 60 minutes, naturally cooled to room temperature, and then rinsed with clean water; wherein the mass fraction of the inorganic acid in the acid solution is 8%, the solvent in the mixed solution is water, platinum is added to the mixed solution as a catalyst, and the mass fraction of the platinum catalyst in the mixed acid solution is 0.6%.
[0045] Example 2
[0046] The difference between this embodiment and embodiment 1 is that the temperature of the strengthening treatment is 200° C., the treatment time is 120 min, and the other conditions are the same as those in embodiment 1.
[0047] Example 3
[0048] The difference between this embodiment and embodiment 1 is that the temperature of the strengthening treatment is 300° C., the treatment time is 60 min, and the other conditions are the same as those in embodiment 1.
[0049] Example 4
[0050] The difference between this embodiment and embodiment 1 is that the temperature of the strengthening treatment is 300° C., the treatment time is 120 min, and the other conditions are the same as those in embodiment 1.
[0051] Example 5
[0052] The difference between this embodiment and embodiment 1 is that the air surface of the float glass is lowered, and other conditions are the same as those of embodiment 1.
[0053] Example 6
[0054] The difference between this embodiment and embodiment 1 is that hydrochloric acid and acetic acid in a molar ratio of 1:2 are used as the acid solution, and other conditions are the same as those in embodiment 1.
[0055] Example 7
[0056] The difference between this embodiment and embodiment 1 is that the float glass is Na2O-Al2O3-SiO2 glass, and other conditions are the same as those in embodiment 1.
[0057] Example 8
[0058] The difference between this embodiment and embodiment 7 is that the temperature of the strengthening treatment is 200° C., the treatment time is 120 min, and the other conditions are the same as those of embodiment 1.
[0059] Example 9
[0060] The difference between this embodiment and embodiment 7 is that the temperature of the strengthening treatment is 300° C., the treatment time is 60 min, and the other conditions are the same as those of embodiment 1.
[0061] Example 10
[0062] The difference between this embodiment and embodiment 7 is that the temperature of the strengthening treatment is 300° C., the treatment time is 120 min, and the other conditions are the same as those of embodiment 1.
[0063] Embodiment 11
[0064] This embodiment provides a surface strengthening process for float glass. Float glass is a Na2O-CaO-SiO2 glass. The strengthening principle of the air surface of float glass is as follows: Figure 1 As shown in the figure, the strengthening principle of the tin surface is as follows Figure 2 As shown, the specific steps are as follows:
[0065] 1) Place the float glass in an air atmosphere containing sulfur dioxide and water at a temperature of 100°C, wherein the volume content of sulfur dioxide is 70% and the volume content of water is 300g / m 2 , the float glass is placed with the air side facing upwards;
[0066] 2) A mixed solution of an inorganic acid (phosphoric acid) with a molar ratio of 2:3 and an inorganic acid (formic acid and citric acid with a molar ratio of 3:1) was heated at 1250 g / m 2 The coating amount is sprayed on the air surface of the float glass, treated for 120 minutes, naturally cooled to room temperature, and then rinsed with clean water; wherein the mass fraction of the inorganic acid in the acid solution is 4%, the solvent in the acid solution is water, platinum is added to the mixed solution as a catalyst, and the mass fraction of the platinum catalyst in the mixed acid solution is 2%.
[0067] Example 12
[0068] This embodiment provides a surface strengthening process for float glass. Float glass is a Na2O-CaO-SiO2 glass. The strengthening principle of the air surface of float glass is as follows: Figure 1 As shown in the figure, the strengthening principle of the tin surface is as follows Figure 2 As shown, the specific steps are as follows:
[0069] 1) Place the float glass in an air atmosphere containing sulfur dioxide and water at a temperature of 200°C, wherein the volume content of sulfur dioxide is 55% and the volume content of water is 400g / m 2 , the float glass is placed with the air side facing upwards;
[0070] 2) A mixed solution of an inorganic acid (nitric acid and carbonic acid in a molar ratio of 1:1) and an inorganic acid (propionic acid and glycolic acid in a molar ratio of 3:1) in a molar ratio of 2:4 was added at 1000 g / m 2 The coating amount is sprayed on the air surface of the float glass, treated for 60 minutes, naturally cooled to room temperature, and then rinsed with clean water; wherein the mass fraction of the inorganic acid in the acid solution is 8%, the solvent in the acid solution is water, aluminum is added to the mixed solution as a catalyst, and the mass fraction of the aluminum catalyst in the mixed acid solution is 0.6%.
[0071] Example 13
[0072] This embodiment provides a surface strengthening process for float glass. Float glass is a Na2O-CaO-SiO2 glass. The strengthening principle of the air surface of float glass is as follows: Figure 1 As shown in the figure, the strengthening principle of the tin surface is as follows Figure 2 As shown, the specific steps are as follows:
[0073] 1) Place the float glass in an air atmosphere containing sulfur dioxide and water at a temperature of 350°C, wherein the volume content of sulfur dioxide is 30% and the volume content of water is 500g / m 2 , the float glass is placed with the air side facing upwards;
[0074] 2) A mixed solution of an inorganic acid (hydrochloric acid) with a molar ratio of 2:4 and an inorganic acid (acetic acid and oxalic acid with a molar ratio of 3:1) was stirred at 420 g / m 2 The coating amount is sprayed on the air surface of the float glass, treated for 10 minutes, naturally cooled to room temperature, and then rinsed with clean water; wherein the mass fraction of inorganic acid in the acid solution is 20%, the solvent in the acid solution is water, zinc is added to the mixed solution as a catalyst, and the mass fraction of the zinc catalyst in the mixed acid solution is 0.2%.
[0075] Comparative Example 1
[0076] The difference between this comparative example and Example 1 is that hydrochloric acid, acetic acid and oxalic acid in a molar ratio of 3:2:1 are used as the acid solution, and other conditions are the same as those in Example 1.
[0077] Comparative Example 2
[0078] The difference between this comparative example and Example 2 is that hydrochloric acid, acetic acid and oxalic acid in a molar ratio of 3:2:1 are used as the acid solution, and other conditions are the same as those in Example 2.
[0079] Comparative Example 3
[0080] The difference between this comparative example and Example 3 is that hydrochloric acid, acetic acid and oxalic acid in a molar ratio of 3:2:1 are used as the acid solution, and other conditions are the same as those in Example 3.
[0081] Comparative Example 4
[0082] The difference between this comparative example and Example 4 is that hydrochloric acid, acetic acid and oxalic acid in a molar ratio of 3:2:1 are used as the acid solution, and other conditions are the same as those in Example 4.
[0083] Comparative Example 5
[0084] The difference between this comparative example and Example 1 is that hydrochloric acid is used as the acid solution, and other conditions are the same as those in Example 1.
[0085] Comparative Example 6
[0086] The difference between this comparative example and Example 2 is that hydrochloric acid is used as the acid solution, and the other conditions are the same as those in Example 2.
[0087] Comparative Example 7
[0088] The difference between this comparative example and Example 3 is that hydrochloric acid is used as the acid solution, and the other conditions are the same as those in Example 3.
[0089] Comparative Example 8
[0090] The difference between this comparative example and Example 4 is that hydrochloric acid is used as the acid solution, and the other conditions are the same as those of Example 4.
[0091] Comparative Example 9
[0092] The difference between this comparative example and Example 1 is that acetic acid and oxalic acid with a molar ratio of 2:1 are used as the acid solution, and other conditions are the same as those in Example 1.
[0093] Comparative Example 10
[0094] The difference between this comparative example and Example 2 is that acetic acid and oxalic acid with a molar ratio of 2:1 are used as the acid solution, and other conditions are the same as those in Example 2.
[0095] Comparative Example 11
[0096] The difference between this comparative example and Example 3 is that acetic acid and oxalic acid with a molar ratio of 2:1 are used as the acid solution, and other conditions are the same as those in Example 3.
[0097] Comparative Example 12
[0098] The difference between this comparative example and Example 4 is that acetic acid and oxalic acid with a molar ratio of 2:1 are used as the acid solution, and other conditions are the same as those in Example 4.
[0099] Comparative Example 13
[0100] The difference between this comparative example and Example 1 is that hydrochloric acid, acetic acid and oxalic acid in a molar ratio of 4:9:3 are used as the acid solution (that is, the molar ratio of the inorganic acid to the organic acid is 1:3), and other conditions are the same as in Example 1.
[0101] Test Example 1
[0102] The glass after strengthening treatment in the above-mentioned embodiment and the comparative example was subjected to surface stress test and glass warpage test. The surface stress test method: the test was conducted according to the glass stress test method of GB / T18144-2008; the glass warpage test method: the strengthened glass was placed at room temperature (25°C) for 4 hours, and then the arc height h and the chord length L of the chemically strengthened glass were measured with a feeler gauge; the glass warpage was expressed as the percentage of the arc height to the chord length. The structural schematic diagram of the glass warpage test is shown in FIG. Figure 3 The surface stress and glass warpage test results are shown in Table 1 below.
[0103] Table 1
[0104]
[0105]
[0106] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A surface strengthening process for float glass, characterized in that: include: The float glass is placed in an oxygen-containing atmosphere containing sulfur dioxide and water and an acid solution is applied to the air surface of the float glass for strengthening treatment; the acid solution is a mixed solution of an inorganic acid and an organic acid, and the molar ratio of the inorganic acid to the organic acid is 2:(3-4).
2. The surface strengthening treatment process according to claim 1, characterized in that: During the strengthening process, the air side of the float glass faces upward.
3. The surface strengthening treatment process according to claim 1 or 2, characterized in that: The oxygen-containing atmosphere includes at least one of air and oxygen; And / or, the coating is spraying; And / or, the coating amount of the acid solution is 420-1250 g / m 2 .
4. The surface strengthening treatment process according to any one of claims 1 to 3, characterized in that: The volume content of the sulfur dioxide is 30-70%.
5. The surface strengthening treatment process according to any one of claims 1 to 4, characterized in that: The water content is 300-500 g / m 2 .
6. The surface strengthening treatment process according to any one of claims 1 to 5, characterized in that: The temperature of the strengthening treatment is 100-350°C; And / or, the duration of the intensive treatment is ≥ 10 min, preferably, the duration of the intensive treatment is 10 to 120 min; And / or, cooling and water washing are further performed after the strengthening treatment.
7. The surface strengthening treatment process according to any one of claims 1 to 6, characterized in that: The inorganic acid includes at least one of hydrochloric acid, sulfuric acid, sulfurous acid, phosphoric acid, nitric acid, and carbonic acid; And / or, the organic acid comprises at least one of formic acid, acetic acid, propionic acid, oxalic acid, citric acid, glycolic acid, and acrylic acid; And / or, a catalyst is further added to the acid solution. Optionally, the catalyst includes at least one of platinum, zinc and aluminum.
8. The surface strengthening treatment process according to claim 7, characterized in that: The organic acids are acetic acid and oxalic acid; And / or, the mass fraction of the platinum catalyst in the acid solution is 0.2-2%.
9. The surface strengthening treatment process according to claim 8, characterized in that: The molar ratio of acetic acid to oxalic acid is 3:
1.
10. The surface strengthening treatment process according to any one of claims 1 to 9, characterized in that: The mass fraction of the inorganic acid in the acid solution is 4 to 20%; And / or, the solvent in the acid solution is water; And / or, the float glass has a thickness of 0.5 to 2 mm.